Deposition And Characterisation Of Solution Processed Indium Gallium Zinc Oxide Thin Film On Silicon Substrate - Kasim, Nabihah (2022)
This research was conducted with an objective to deposit optimum polycrystalline indium gallium zinc oxide (IGZO) on silicon (Si) substrate by using solution processed method. Specifically, sol-gel method was selected to prepare IGZO precursor solution and spin coating method was used to deposit the film.